Transformation of the Minangkabau Islamic Education: The Study of Educational thought of Abdul Karim Amrullah, Abdullah Ahmad And Rahmah El-Yunusiyah - Zulmuqim Zulmuqim (Institut Agama Islam Negeri Imam Bonjol Padang, 2015)
Transformation of education in Minangkabau at the Beginning the 20th Century was done by established figure of Islam, such as Abdul Karim Amrullah, Abdullah Ahmad and Rahmah el-Yunusiyah. Abdul Karim Amrullah begins transforming Islamic education by changing the status of Jembatan Besi Surau to become Islamic modern school (Madrasah) with class system, which is known as Sumatera Thawalib. Abdullah Ahmad transforms Islamic education by establishing HIS Adabiyah with school system, and also includes Islamic subjects in the curriculum. Moreover Rahmah el-Yunusiyah committed renewal by building woman Islamic school (Madrasah).Â Key words:Renewal, Islamic Education, Education Thinking.Copyright Â© 2015 by Al-Ta'lim All right reserved